1996
DOI: 10.1021/ma951625y
|View full text |Cite
|
Sign up to set email alerts
|

The Very Long-Term Volume Recovery of Polycarbonate:  Is Self-Retardation Finite?

Abstract: The specific volume change of Bisphenol A polycarbonate was measured at room temperature for several years. The effects of formation conditions like cooling rate and pressure, the addition of low molecular additives, and injection molding and quenching were investigated. The volume shrinkage at long times was found to be much higher than extrapolated from short term measurements. A general pattern is observed in the volume recovery curves. They start with a small constant slope on the logarithmic time scale. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 19 publications
10
30
0
Order By: Relevance
“…In conclusion it is worth comparing our permittivity data with the volume relaxation data already reported in literature [23]. In this study, no specific volume reduction is observed for PC volume relaxation at 25°C in the time scale of several days, which is the time scale for our permittivity relaxation experiments.…”
Section: Discussionsupporting
confidence: 77%
“…In conclusion it is worth comparing our permittivity data with the volume relaxation data already reported in literature [23]. In this study, no specific volume reduction is observed for PC volume relaxation at 25°C in the time scale of several days, which is the time scale for our permittivity relaxation experiments.…”
Section: Discussionsupporting
confidence: 77%
“…At 423 K, the apparent aging rate accelerates after 300 min as shown in Figure (a), which is counter to the typical slowdown in aging in the terminal region . There have been similar reports for acceleration in the densification of polycarbonates after long aging times (>10 7 s) . Here, this change in the apparent aging rate is accompanied by chemical modification of the polymer (Supporting Information, Fig.…”
Section: Resultssupporting
confidence: 51%
“…Recent work (15) on polycarbonate (PC) suggests otherwise. At low aging temperatures, volume recovery appeared to be higher than expected (15). In addition, there was a sharp transition from a slow rate of volume recovery to a much faster aging rate at 10 7 s. The observations have been confirmed qualitatively for polycarbonate but not for polystyrene (PS) (16).…”
Section: Aging Physical 295mentioning
confidence: 77%
“…For enthalpy recovery, (dδ/dP) T = VT α and (dδ/dT) P = C p . The nonexponentiality of the structural recovery process is described by the nonexponentiality parameter β in equation (15); the history dependence is accounted for by the integral of the reduced time (dt/τ ); and the nonlinearity is incorporated into the model by allowing the characteristic relaxation time τ Vol. 1…”
Section: Modeling Structural Recoverymentioning
confidence: 99%